A qualidade da alimentação e fatores antropométricos, socioeconômicos e de saúde em crianças de 7 a 9 anos de idade - Paixao, Fernando Barbosa de Souza (2023)
A dietary pattern characterized by high consumption of ultra-processed foods, sugary beverages, and low intake of natural foods has been observed among children. These changes in dietary quality and a sedentary lifestyle are proposed as key etiological factors contributing to childhood obesity and weight-related chronic diseases. A diverse and high-quality diet is considered effective in reducing the risk of childhood overweight. Therefore, it is crucial to apply methods to assess diet quality and identify other factors that may influence weight gain in children. Understanding how these variables affect children's health and food choices can guide the development of future interventions for this population, ultimately improving their quality of life and contributing to the cultivation of healthy adults. Objective: To evaluate the relationship between diet quality and anthropometric, socioeconomic, and health factors in children aged 7 to 9 years. Method: This was a cross-sectional study conducted among children aged 7 to 9 years. Data on socioeconomic status, anthropometric measurements, sleep habits, screen time, and dietary habits were collected. Descriptive data analysis was performed, followed by inferential analyses using the Chi-squared test and multinomial logistic regression. Results: A total of 336 children aged 7 to 9 years were evaluated, comprising 157 (46.7%) boys and 179 (53.3%) girls. Regarding diet quality, 109 (32.4%) children had a low-quality diet, 135 (40.2%) had a moderate-quality diet, and 92 (27.4%) had a high-quality diet. A statistically significant difference was found between screen time and diet quality for both boys and girls (pvalue 0.010 and 0.025, respectively). Multinomial logistic regression revealed that boys with appropriate screen time had a 7.54 times higher chance of having a high-quality diet, while girls had a 3.26 times higher chance. Conclusion: Children's diet quality may be influenced by screen time. However, diet quality was not associated with BMI and other variables. Further studies are needed to better investigate how prolonged exposure to electronic devices may affect the food choices of these children and promote weight gain.